1986
DOI: 10.1111/j.1365-2621.1986.tb10871.x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration and Separation of Grape Pomace in a Fluidized Bed System

Abstract: Grape pomace components (seed and skin) were separated in a fluidized bed system based on their aerodynamic behavior. The Weibull equation was used to explain the elutriation history. Seed dehydration was characterized by a first period of constant drying rate and a second period in which drying rate decreased following Fick's liquid molecular diffusion model. The order of magnitude of heat and mass transfer parameters, both internal and external, was similar to those reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results of Box and Lucas (1959) for the first-order reaction model and those of Cunha et al (1997) for the isothermal Thermal Death Time model, showed that when analysing a given system over a range of temperatures, an experiment should Chhinnan (1984); q , Heinz and Knorr (1996); o, Ilincanu et al (1995); A, Li and Morey (1984); l , Machado et al (1997); o, Misra and Brooker (1980); +, Peraza et al (1986); l , Shepherd and Bhardwaj (1988); and w, White et al (1981).…”
Section: Set Of Isothermal Experiments Conducted Over a Range Of Tempmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of Box and Lucas (1959) for the first-order reaction model and those of Cunha et al (1997) for the isothermal Thermal Death Time model, showed that when analysing a given system over a range of temperatures, an experiment should Chhinnan (1984); q , Heinz and Knorr (1996); o, Ilincanu et al (1995); A, Li and Morey (1984); l , Machado et al (1997); o, Misra and Brooker (1980); +, Peraza et al (1986); l , Shepherd and Bhardwaj (1988); and w, White et al (1981).…”
Section: Set Of Isothermal Experiments Conducted Over a Range Of Tempmentioning
confidence: 99%
“…To model the simultaneous effect of drying and separation of grape pomace in a fluidised bed, Peraza et al (1986) have used the Weibull model, as mentioned in the introduction. In this work, they have measured as a response function the grape skin fraction in the bed at any time (q) and modelled grape pomace elutriation as a function of fluidisation velocity (ur) and length/diameter ratio (L/D) of the fluidised bed.…”
Section: Separation Of Grape Pomace In a Fluidised Bedmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend of superior capitalization of wine by-products has led to the development of various separation methods that use complex equipment, which includes in their components systems for prepreparation of the seed mixture before the actual separation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%